Jadal as-SimÄh dÅ«na á¸¤aml ar-RimÄá¸¥: DirÄsah fÄ« Makhá¹Å«á¹ah al-Manhil al-âaÅ¼b li Å¼ikr al-Qalb li asy-Syaikh IsmÄâÄ«l al-Minangkabawi - hadi, syofyan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
Since the beginning of his arrival in the archipelago, the scholars involved in the initial process of spreading Islam have emerged with an offer of a variety of religious understandings. Such diversity and differences are sometimes not uncommon to bring followers into horizontal friction to conflict and even bloodshed. Animosity and tension caused by differences in religious understanding and practice even continued for several generations with various levels and levels of conflict as a result among Islamic community in the archipelago. The feud and tension of religious understanding that took place between Shaykh Ismail al-Minangkabawi and Shaykh Salim bin Samir al-Hadhrami, Shaykh Abd al-Ghani Bima, Shaykh Abd al-Azhim Madura which occurred in the 19th century were among the evidence of continued conflict in religious understanding between the scholars who spread Islam in the archipelago. However, this religious conflict is only within the limits of dialogue and debate without dragging followers to something that has the negative impact of confrontation or bloodshed. At the very least, these debate and dialogue were the ones described by Shaykh Ismail al-Minangkabawi and the opponents of his teachings in the archipelago.